Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Bé cảm ơn
Akai Haruma
30 tháng 10 2024 lúc 12:50

Lời giải:

Áp dụng định lý Viet:

$x_1+x_2=3$

$x_1x_2=-7$

Khi đó:

$A=x_1^2+x_2^2=(x_1+x_2)^2-2x_1x_2=3^2-2(-7)=23$
$B=|x_1-x_2|=\sqrt{(x_1-x_2)^2}=\sqrt{(x_1+x_2)^2-4x_1x_2}$

$=\sqrt{3^2-4(-7)}=\sqrt{37}$

$C=\frac{1}{x_1-1}+\frac{1}{x_2-1}=\frac{x_1+x_2-2}{(x_1-1)(x_2-1)}=\frac{x_1+x_2-2}{x_1x_2-(x_1+x_2)+1}$

$=\frac{3-2}{-7-3+1}=\frac{1}{-9}$

$D=(3x_1+x_2)(3x_2+x_1)=10x_1x_2+3(x_1^2+x_2^2)$

$=10(-7)+3.23=-1$

$E=x_1^3+x_2^3=(x_1+x_2)^3-3x_1x_2(x_1+x_2)$

$=3^3-3(-7).3=90$

$F=x_1^4+x_2^4=(x_1^2+x_2^2)^2-2(x_1x_2)^2=23^2-2(-7)^2=431$


Các câu hỏi tương tự
Xuân Thường Đặng
Xem chi tiết
Thảo Thảo
Xem chi tiết
Nguyên
Xem chi tiết
Đỗ Thành Đạt
Xem chi tiết
Pham Trong Bach
Xem chi tiết
gh
Xem chi tiết
LovE _ Khánh Ly_ LovE
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Trần Thủy Tiên
Xem chi tiết